A Comparative Study of the Effects of Reflexology Massage and Rose Aromatherapy on Pain Severity in Patients Undergoing Gastric Bypass surgery in Amin Hospital of Isfahan University of Medical Sciences, 2021 - Arezoo Hassanpour Esfahani; Seyed ali Naji (Hamadan University of Medical Sciences, 2022)
Background and Objective: Obesity surgery is the most effective treatment for obese people. Patients are exposed to various painful therapeutic interventions during hospitalization; moreover, postoperative pain is a common complaint among these patients. The present study aimed to compare the effect of reflexology massage and aromatherapy of rose on the severity of pain in women undergoing gastric bypass surgery in Amin Hospital of Isfahan University of Medical Sciences in 1400. Materials and Methods: Thie current study was conducted based on a quasi-experimental design. The statistical population included women undergoing gastric bypass surgery in Amin Hospital affiliated with Isfahan University of Medical Sciences in 1400. The participants were selected by the available sampling method and the sample size was calculated at 31 cases in each group. The instrument used to determine pain intensity was the Visual Analog Scale (VAS). In the reflexology group, relaxation techniques were used for six minutes and the massage was then used to reduce pain. In aromatherapy, two drops of rose oil were poured on a sterile gauze and the patient was asked to inhale it from a distance of 7-10 cm for 20 min. In both groups, pain intensity was measured using the VAS immediately before and after the intervention. All obtained information was analyzed in SPSS software (version 26) using descriptive statistics(mean, standard deviation, and frequency) and analytical statistics ( Kolmogorov-Smirnov, paired t-test, and independent t-test). Results: The results of the analysis demonstrated that at a 95% confidence level in both reflexology and aromatherapy groups, the mean pain intensity before the intervention was higher than that after the intervention (P<0.001). The comparison of the difference between the mean pain intensity before and after the intervention in the two groups under study pointed out that this difference was significantly higher in the group under reflexology massage (P<0.001). Conclusion: As evidenced by the results of the present study, reflexology massage is more effective than aromatherapy in the reduction of pain in women undergoing gastric bypass surgery. The use of this treatment is recommended to all members of the treatment team.